2017
DOI: 10.18553/jmcp.2017.16265
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Opioid Abuse: Updated Findings

Abstract: This study was funded by Purdue Pharma. Mayne is an employee of Purdue Pharma. Kirson, Scarpati, and Birnbaum are employees of Analysis Group, which received funding from Purdue Pharma to conduct this study. Enloe and Dincer were employees of Analysis Group at the time this research was conducted. Study concept and design were contributed by Kirson, Birnbaum, Mayne, and Scarpati, along with Enloe and Dincer. Enloe and Dincer took the lead in data collection, along with Birnbaum and assisted by Kirson and Scarp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 12 publications
3
39
0
1
Order By: Relevance
“…Additionally, several matched cohort studies reported direct healthcare costs over a 12-month follow-up period that consisted of a 6-month period prior to and a 6-month period following a patient’s index date, which was defined as the date of the first formal abuse diagnosis. The total healthcare cost difference between abusers and matched non-abuser controls began to increase prior to the index date, with excess costs of more than US$3000 per person in the pre-index period [ 17 , 18 , 21 , 22 , 25 ]. Following the initial diagnosis of abuse, this cost difference increased substantially to US$7971–US$12,727 per person in the post-index period [ 17 , 18 , 21 , 22 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several matched cohort studies reported direct healthcare costs over a 12-month follow-up period that consisted of a 6-month period prior to and a 6-month period following a patient’s index date, which was defined as the date of the first formal abuse diagnosis. The total healthcare cost difference between abusers and matched non-abuser controls began to increase prior to the index date, with excess costs of more than US$3000 per person in the pre-index period [ 17 , 18 , 21 , 22 , 25 ]. Following the initial diagnosis of abuse, this cost difference increased substantially to US$7971–US$12,727 per person in the post-index period [ 17 , 18 , 21 , 22 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Opioid abuse leads to an estimated additional $14,810 in per-patient annual health care costs due to higher health care utilization. 7 In patients undergoing plastic and reconstructive surgery, risks for persistent (between 90 and 180 days after surgery) and prolonged (more than 180 days after surgery) use include being prescribed an opioid in the perioperative setting, procedure type, number of medical comorbidities, and history of mental health disorders or substance abuse. 8 Although work has been done to characterize rates of perioperative opioid use after radical prostatectomy, data on persistent and prolonged opioid use are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Alarmingly, illicit fentanyl products are increasingly identified in products sold as heroin [3]. As more people are affected by this crisis, many eventually interact with the healthcare system, often for acute care needs [4,5].…”
Section: Introductionmentioning
confidence: 99%